2018
DOI: 10.1021/acs.jpcb.7b09716
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of the Oil-Detachment from the Hydroxylated Silica Surface: Effects of Surfactants, Electrostatic Interactions, and Water Flows on the Water Molecular Channel Formation

Abstract: The detachment process of an oil molecular layer situated above a horizontal substrate was often described by a three-stage process. In this mechanism, the penetration and diffusion of water molecules between the oil phase and the substrate was proposed to be a crucial step to aid in removal of oil layer/drops from substrate. In this work, the detachment process of a two-dimensional alkane molecule layer from a silica surface in aqueous surfactant solutions is studied by means of molecular dynamics (MD) simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 61 publications
0
23
0
1
Order By: Relevance
“…Among others, adding extra chemicals (surfactant, polymer) can effectively adjust the property of injecting fluids, and meanwhile change the composition of capillary surface with their adsorption, which is thus efficient in regulating two-phase displacement process. 14,15 Currently, the development of new chemical fluids to regulate two-phase displacement involves a major challenge, as many studies observed that the efficiency of chemical fluid is capillary dependent. For example, according to the worldwide enhanced oil recovery (EOR) survey, not all the reservoirs can adopt same chemical fluids, and the performance of a specific chemical fluid varies significantly in different capillaries.…”
Section: Introductionmentioning
confidence: 99%
“…Among others, adding extra chemicals (surfactant, polymer) can effectively adjust the property of injecting fluids, and meanwhile change the composition of capillary surface with their adsorption, which is thus efficient in regulating two-phase displacement process. 14,15 Currently, the development of new chemical fluids to regulate two-phase displacement involves a major challenge, as many studies observed that the efficiency of chemical fluid is capillary dependent. For example, according to the worldwide enhanced oil recovery (EOR) survey, not all the reservoirs can adopt same chemical fluids, and the performance of a specific chemical fluid varies significantly in different capillaries.…”
Section: Introductionmentioning
confidence: 99%
“…The utility of MD simulations for petroleum engineering is well recognized and numerous studies have been reported concerning the properties of oil–water and oil–mineral interfaces, including surfactants. ,, There are comparatively fewer reports specifically focused on the wettability alteration of initially oil-wet surfaces by surfactants, which, moreover, rely on models that seem to largely disregard the experimentally well-documented and generally accepted properties of the minerals, the oil, as well as the mechanisms of the interaction between the two. In particular, rather than using the most naturally abundant {1,0,1̅,4} calcite surface , to model the carbonate substrate, a different and apparently arbitrary {1,0,0} plane is used.…”
Section: Introductionmentioning
confidence: 99%
“…52 The transport of ions across the interface is usually initiated by compounds such as surfactants and lipophilic complexes, inducing the formation of specific interfacial structures, for instance a water channel. 51,53,54 These specific interfacial structures bring a challenge for the free energy calculation. Recently, combined with MD simulations, some enhanced sampling methods such as replica exchange, 55 accelerated molecular dynamics, 56 umbrella sampling, 57 and metadynamics 58 have been proposed and developed to obtain a more accurate description of the free energy during ion transfer across interfaces.…”
Section: Introductionmentioning
confidence: 99%